The Role of Scientific Research in Achieving Sustainable Development According to the Kingdom of Saudi Arabia’s Vision 2030 from the Point of View of Faculty Members at the University of Ha’il - Mustafa, Jehan Hazim Habib; Maali, Sanaa Mahmood; Ghazy, Amal Abdelkader; ElHadiede , Nesreen Abdou; Aldaw, Muna Hasssn Babiker (Journal of Ecohumanism, 2025)
The study aimed to identify the role of scientific research in achieving the goals of sustainable development in light of the Kingdom of Saudi Arabia’s Vision 2030 from the point of view of faculty members at the University of Ha’il.The study relied on the descriptive analytical approach, and to achieve the goal of the study, a questionnaire was developed consisting of 20 items distributed over three axes; The development and growth of universities, developing human resources and increasing the quality and number of research. The questionnaire was distributed to 200 faculty members at the University of Ha’il, after ensuring its validity and reliability. The questionnaire data was processed statistically using means, standard deviations, and an equation of Cronbach alpha. The results of the study concluded that scientific research plays an important and fundamental role in sustainable development in the Kingdom from the point of view of faculty members, especially with what the Kingdom seeks towards its ambitious 2030 vision. The researchers recommended that the university support research to achieve the requirements of sustainable development, address issues related to community problems, and link them to development plans.